Developing Islamic Religious Education Strategies to Enhance Students’ Learning Motivation in the Digital Era - Hilalludin Hilalludin; Shada Al Nomani; Miftahus Sulhi (STKIP Pesisir Selatan, 2026)
This study aims to develop effective Islamic Religious Education (IRE) strategies to enhance students’ learning motivation in the digital era through a qualitative case study across Indonesia, Turkey, and Saudi Arabia. The research focuses on understanding how different educational contexts implement learning strategies and how these strategies influence student motivation. Data were collected through observation, in-depth interviews, and documentation involving students, teachers, and educational experts. The findings reveal that students’ learning motivation is significantly influenced by four key factors: digital integration, student-centered learning approaches, the strategic role of teachers, and the contextualization of religious values. Turkey demonstrates the most effective model by integrating interactive digital tools with student-centered pedagogy, resulting in high intrinsic motivation. Saudi Arabia shows strong technological support and structured learning environments, although motivation tends to be more extrinsically driven. Meanwhile, Indonesia reflects a transitional stage, where digital tools are utilized but not yet optimally integrated into pedagogical practices. The study concludes that effective IRE strategies in the digital era require a holistic approach that combines technological innovation, active learning, teacher facilitation, and meaningful content. These findings contribute to the development of more adaptive and engaging IRE practices and provide practical implications for educators and policymakers. Future research is recommended to explore experimental designs and long-term impacts of digital-based IRE strategies.